Body mass changes and nutrient intake of dinghy sailors while racing - Slater, G.; Tan, B. (Journal of Sports Sciences, 2007)
Dinghy sailing is a physically challenging sport with competitors on water for several hours. Regulations and space in the boat limit the amount of food and fluid competitors can carry. Consequently, it is possible that the hydration and nutritional status of dinghy sailors may be compromised while racing. Despite this, the food and fluid intake of sailors while racing are unknown. The aim of this study was to assess the dietary intake of a group of club sailors while racing and compare this with current sports nutrition guidelines. Thirty-five sailors (9 females, 26 males) were monitored during a club regatta. Body mass changes were measured before and after racing, as were food and fluid intake. Results showed that most participants were in negative fluid balance after racing (males: mean -2.1%[95% confidence limits -1.7 to -2.5%]; females: -0.9%[0 to -1.8%]), most likely due to low voluntary fluid intake (males: 1215 ml [734 to 1695 ml]; females: 792 ml [468 to 1117 m]). Carbohydrate intake (males: 59 g [21 to 97 g]; females: 30 g [0 to 61 g]) was below recommendations for normal sports activity. Results revealed that the nutritional practices of club sailors do not comply with current sports nutrition guidelines. However, the performance implications of a compromise in nutrient intake remain to be investigated. Practical advice on methods of overcoming space limitations for the carriage of adequate fluid and food is offered.